Hak Atas Kekayaan Intelektual sebagai Benda Wakaf - Juju Jumena; Mia Siti Sumiati Dewi (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2017)
The wakaf is a wortshop based on social-religious values. The wakaf legislation rules in Indonesia regulted by Act no. 41 of 2004 on wakaf whichexpanding of wakaf objects in the form of moving objects which one of them is Intellectual Property Rights (IPRs). The term of IPRs is not known in Islamic Law. Seeing the problem, the writer feels the need to study more deeplyabout IPRs wakaf in the Islamic law, especially in Hanafiyah School. This research is library research with qualitative method and normative juridical approach. The preparation data of this research has descriptive-analytis-comparative. From this research, the muta’akhirin priests of Hanafiyah School, IPRs wakaf is allowed, because the IPRs included to the objects and have economic value on the basis of the 'urf. According to the positive law, IPRs can be categorized as wakaf in accordance with wakaf Legislation. The similarity of IPRs wakaf in Hanafiyah School and wakaf Legislation is the temporal nature in wakaf, the permanent ownership of wakaf and nazir items which may benefit from the wakaf they manage in a good way. The difference of IPRS waqf in Hanafiyah School and wakaf Legislation are in the essential terms, dependent on the status of wakaf objects, wakaf that may be with drawn, sold and inherited and the administrative system of wakaf.